The Impact of COVID-19 on Hospitalised COPD Exacerbations in Malta. (29th June 2021) - Farrugia, Yvette; Spiteri Meilak, Bernard Paul; Grech, Neil; Asciak, Rachelle; Camilleri, Liberato; Montefort, Stephen; Zammit, Christopher
Abstract : Introduction and Aims. The first COVID-19 case in Malta was confirmed on the 7th of March 2020. This study is aimed at investigating a significant difference between the number of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) admissions and their inpatient outcome at Mater Dei Hospital during the COVID-19 pandemic when compared to the same period in 2019. Furthermore, we aim to determine predictors of mortality in AECOPD inpatients. Method . Data was collected retrospectively from electronic hospital records during the periods 1st March until 10th May in 2019 and 2020. Results . There was a marked decrease in AECOPD admissions in 2020, with a 54.2% drop in admissions (n = 119 in 2020 vs. n = 259 in 2019). There was no significant difference in patient demographics or medical comorbidities. In 2020, there was a significantly lower number of patients with AECOPD who received nebulised medications during admission (60.4% in 2020 vs. 84.9% in 2019; p ≤ 0.001 ). There were also significantly lower numbers of AECOPD patients admitted in 2020 who received controlled oxygen via venturi masks (69.0% in 2020 vs. 84.5% in 2019; p = 0.006 ). There was a significant increase in inpatient mortality in 2020 (19.3% [n = 23 ] and 8.4% [n = 22 ] for 2020 and 2019, respectively, p = 0.003 ). Year was found to be the best predictor of mortality outcome (p = 0.001 ). The lack of use of SABA pre-admission treatment (p = 0.002 ), active malignancy (p = 0.003 ), and increased length of hospital stay (p = 0.046 ) were also found to be predictors of mortality for AECOPD patients; however, these parameters were unchanged between 2019 and 2020 and therefore could not account for the increase in mortality. Conclusions . There was a decrease in the number of admissions with AECOPD in 2020 during the COVID-19 pandemic, when compared to 2019. The year 2020 proved to be a significant predictor for inpatient mortality, with a significant increase in mortality in 2020. The decrease in nebuliser and controlled oxygen treatment noted in the study period did not prove to be a significant predictor of mortality when corrected for other variables. Therefore, the difference in mortality cannot be explained with certainty in this retrospective cohort study.